Affordable Automation: Strategies for Cost Reduction and Efficiency Improvement in Daily Robotics - Garima Kachhara; Panini Kashyap; Nipun Sharma; Parul Jain (International Journal of Robotics and Automation in Mechanics, 2025)
The study examined how robotics technologies can increase productivity in industries. As we all know, artificial intelligence (AI) is on the rise in the market, and industries are becoming increasingly reliant on AI to handle multifaceted tasks. Robotics is one of the most prominent fields in manufacturing and science, where engineers are focusing on developing robots that can perform specific tasks and deliver accurate results. As technology progressed, by 2005, 90% of all robots were used in car assembly in automotive factories. Today, robots serve a wide range of purposes, including healthcare, space exploration, and military applications. In the future, robotics and sensor technologies are expected to advance significantly, along with machine learning and AI capabilities, becoming even more impressive and sophisticated. This study aims to provide an overview of the field of robotics. The researcher concluded that robotics is revolutionizing the future of work across various industries. In many ways, robots have become an integral part of daily life.
Keywords: Autonomous; Robotics; artificial intelligence; cost-cutting; efficiency; manufacturing; sustainable